STRATEGY MANAGEMENT DEVELOPMENT INCREASING TEACHERS' PROFESSIONAL COMPETENCE - Salni; Asep Saepul Hidayat (Jurnal Pendidikan Sang Surya, 2024)
ABSTRACT: Teacher professional competence is important in the implementation of education, school work productivity, learning effectiveness and the quality of graduates at every educational institution. However, the reality is that the demands of the development of science and technology, the limited conditions of schools, the condition of students and the weak supporting capacity, indirectly pose challenges to the management of school principals. This research focuses on examining the development of strategic management in an effort to increase teacher professional competence. Through a qualitative approach and technical support from case studies, this research resulted in the conclusion that: the development of strategic management carried out by school principals in improving teacher professional competence must pay attention to (1) strategic planning that focuses on teacher performance output efforts; (2) the strategy to increase teacher professional competence is carried out using a multi-strategy because of changes in teachers' conditions and needs are always changing; (3) Determining the main targets for increasing teacher professional competence, apart from the main elements of teacher professionalism, is also developed in accordance with conditions, situations, demands and needs as well as optimizing the achievement of learning objectives